THE IMPORTANCE OF LOCAL AND INTERNATIONAL ENGAGEMENT IN BUILDING A "SUCCESSFUL" UNIVERSITY - Knight, Jane (My University, 2014)
"The notion of a 'successful university' is both comprehensive and evasive. A 'successful university' means different things to students, faculty, academic leaders, citizens, decision makers across various disciplines, sectors and countries around the world. Often success is in the eye of the beholder - or perhaps more importantly - stakeholder. Those who attempt to define, measure, and predict success need to be mindful of Einstein's famous 1902 quote - "Not everything that can be counted counts, and not everything that counts can be counted."" - ...
Keywords: Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education::International education; higher education, Kazakhstan; successful university; research; innovation; research and innovation; the teaching and learning process